2009
DOI: 10.1080/00207450802325843
|View full text |Cite
|
Sign up to set email alerts
|

Whole Brain Size and General Mental Ability: A Review

Abstract: We review the literature on the relation between whole brain size and general mental ability (GMA) both within and between species. Among humans, in 28 samples using brain imaging techniques, the mean brain size/GMA correlation is 0.40 (N = 1,389; p < 10 −10 ); in 59 samples using external head size measures it is 0.20 (N = 63,405; p < 10 −10 ). In 6 samples using the method of correlated vectors to distill g, the general factor of mental ability, the mean r is 0.63. We also describe the brain size/GMA correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(138 citation statements)
references
References 151 publications
(152 reference statements)
6
126
2
4
Order By: Relevance
“…Within humans [20] and across primates [5], it has been shown convincingly that a general factor of cognitive abilities in the physical domain [21] shows a much stronger correlation with absolute than relative brain size. However, it may be a primate peculiarity that the absolutely largest species are also the most intelligent ones.…”
Section: Are Marsupials Smaller-brained Than Their Placental Cousins?mentioning
confidence: 98%
“…Within humans [20] and across primates [5], it has been shown convincingly that a general factor of cognitive abilities in the physical domain [21] shows a much stronger correlation with absolute than relative brain size. However, it may be a primate peculiarity that the absolutely largest species are also the most intelligent ones.…”
Section: Are Marsupials Smaller-brained Than Their Placental Cousins?mentioning
confidence: 98%
“…In seeking to explain gender differences in cognitive abilities, some scholars have cited societal factors, cultural differences, and gender stereotypes; as well as biological factors, such as differences in prenatal hormonal influences and brain size and structure (Ankney 1992;Alonso-Nanclares et al 2008;Rushton and Ankney 2009;Tapp et al 2011;Miller and Halpern 2014). In light of evidence showing that these differences vary substantially across nations, and mirror the gender inequalities in education, employment opportunities, and career achievements in particular countries, researchers have suggested that improved standards of living and educational opportunities in populations with lower economic development levels may improve the cognitive performance levels in these populations, especially among women (Baker and Jones 1993;Else-Quest et al 2010;Weber et al 2014).…”
Section: Sex Differences In Cognitive Functionmentioning
confidence: 99%
“…Furthermore, it is believed that humans have experienced the increase in cortical surface size in evolutionary response to demands in the cognitive requirements (Rushton and Ankney, 2009), supported by consistent reports of positive correlations between whole-brain size and measures of intelligence (Witelson et al, 2006). Thus, if schizophrenia, and bipolar disorder to some extent, are neurodevelopmental disorders in which disruption of higher cognitive functioning is a core feature, abnormalities in normal cortical surface development may play a role in the pathophysiology of the diseases and, hence show disrupted relationships with neurocognitive performance.…”
Section: Developmentmentioning
confidence: 99%